Superstition, Conspicuous Spending, and Housing Markets: Evidence from Singapore - Sumit Agarwal; Jia He; Haoming Liu; Ivan P. L. Png; Tien Foo Sing; Wei-Kang Wong (Institute for the Study of Labor (IZA), 2016)
For most people, buying a home is their single largest financial commitment. Previous research shows that Chinese buyers pay less for homes with unlucky addresses and more for homes with lucky addresses. Using Singapore data on housing transactions combined with a plethora of individual buyer characteristics including ethnicity, age, nationality, education, and employment, we study the source of these preferences. We find evidence that buyers are heterogeneous. Consistent with superstition, older people, those who suffered from more traffic accidents, and people buying new apartments have stronger preference for lucky addresses, while people with Western names and senior public-sector employees have weaker preference. Consistent with conspicuous spending, people with Western names, senior public-sector employees, and people buying in luxury districts have weaker preference for lucky addresses.
Keywords: D1; R3; Z1; 330; superstition; conspicuous spending; real estate; prices; behavioral economics